Alternate cropping system: A tool to enhance income - Meena, L R; Subash, N; Kumar, Devendra; Meena, Sampat Ram; Meena, Adarsh Kumar (Indian Farming, 2023)
The current cropping systems lack long-term productivity and profitability guarantees. Monocropping adoption brings issues like resource underutilization, low profits, emergence of diseases and pests, and vulnerability to climate change. Soil fertility indicators have been negatively impacted by mono cropping. To improve crop productivity and profitability, adopting alternative cropping systems is crucial. Introducing new crops, advanced production technologies, and diversification strengthens farmers. Efficient cropping systems increase yield, drought resilience, water and nutrient management, pest resistance, biodiversity, and food security. Crop diversification facilitates access to domestic and international markets. It also offers nutritional benefits and promotes self-reliance in food production. Replacing monocropping with high-value crops in diversified systems helps manage market pricerisks while ensuring sustainable profitability for farmers.